Corticosteroid Use and Periodontal Disease: A Systematic Review - Brasil-Oliveira, Rebeca; Cruz, Álvaro A.; Sarmento, Viviane Almeida; Souza-Machado, Adelmir; Lins-Kusterer, Liliane (European Journal of Dentistry, 2020)
Periodontitis affects the teeth supporting structures, such as periodontal tissues. We aimed to evaluate the association between periodontal disease and corticosteroid use. We searched in MEDLINE, Web of Sciences, SCOPUS, LILACS, and Cochrane databases, using the descriptors “Periodontal diseases” AND (“adrenal cortex hormones” OR “adrenal cortex hormones” OR (“adrenal” AND “cortex” AND “hormones”) OR “adrenal cortex hormones” OR “corticosteroid”). We selected the summaries of observational studies, addressing periodontal disease in patients using corticosteroids. The search resulted in 403 articles. After applying the selection criteria, eight studies remained; being two retrospective cohorts and six cross-sectional studies. There are few studies with appropriate methodology to produce sound evidence about the causal relationship between the use of corticosteroids and periodontitis. However, two retrospective cohorts confirmed that chronic corticosteroid use is associated with the incidence of periodontal disease. Dental staff must be aware of this association for better management of periodontal disease therapy in patients using corticosteroids.
Keywords: periodontal disease; corticosteroid; review